Solve: 6(x - 2) + 3(x - 2) = 18: (A) x=22/9 (B) x=2 (C) x=4

s

Rating

3

6(x - 2) + 3(x - 2) = 18

6x - 12 + 3x - 6 = 18

9x = 18 + 12 + 6

x = 36/9 = 4

6x - 12 + 3x - 6 = 18

9x = 18 + 12 + 6

x = 36/9 = 4

Added 3/5/2014 8:43:11 PM

This answer has been confirmed as correct and helpful.

Confirmed by alfred123 [3/5/2014 8:43:27 PM]

Find the difference. (4x2 + 3x + 2) - (2x2 + 2x + 1): (A) 2x2 + 5x + 3 (B) 2x2 + x + 1 (C) 2x2 - x - 1

Question|Asked by renaryoko

Updated 3/5/2014 8:46:37 PM

1 Answer/Comment

Multiply: (3x - 6)(2x + 7): (A)6x2 + 9x - 42 (B)6x2 + x - 42 (C) 6x2 - 42

Question|Asked by renaryoko

Updated 3/5/2014 8:44:51 PM

1 Answer/Comment

31,452,209

questions answered

denyang

$462.55

Hearts 10,159 Views 2,016,773 Streams 613

sujaysen

$376.30

Hearts 8,372 Views 2,029,930 Streams 648

Flora1988

$338.00

Hearts 7,442 Views 2,416,897 Streams 738

miyaka

$325.90

Hearts 6,879 Views 3,021,018 Streams 900

PeachyStream97

$317.05

Hearts 6,830 Views 1,047,324 Streams 318

sampi1890

$315.05

Hearts 6,746 Views 3,411,027 Streams 932

maydj

$314.30

Hearts 6,791 Views 2,683,040 Streams 773

phpmicro

$244.70

Hearts 5,045 Views 1,922,794 Streams 516

There are no comments.